The Design of Stacking Yards Management of The Early Warning System Model: A case study in Jakarta International Container Terminal, Indonesia - Arief Witjaksono; Marimin Marimin; Machfud Machfud; Sri Rahardjo (International Journal of Supply Chain Management, 2017)
As a part of the Indonesia-National Logistics System, Jakarta International Container Terminal (JITC), facing a long dwell time which impacts to high yard occupancy ratio (YOR). This is happened because of the long necessary documents of clearance processing time, the limited yard provided, and the owners preferring for storing their goods in the terminal for cost reasons, etc. The objectives of this research are to design an early warning system model to avoid YOR above the normal by using adaptive neuro fuzzy inference system (ANFIS); designing the inter-agency institutional collaboration to apply the model by using interpretive Structural Modeling (ISM); and formulating YOR above normal mitigation strategy. The primary data used are collected through the in-depth interviews and the focus group discussions with the multi-discipline experts. The secondary data are collected from JITC daily operations and from other supporting agencies. The proposed model is validated, verified and tested. It shows the promising results. Keywords: dwell time, yard occupancy ratio, institution model, ANFIS, ISM.